Tumor cell network integration in glioma represents a stemness feature - Xie, Ruifan; Keßler, Tobias; Grosch, Julia Katharina; Hai, Ling; Venkataramani, Varun; Huang, Lulu; Hoffmann, Dirk C.; Solecki, Gergely; Ratliff, Miriam; Schlesner, Matthias; Wick, Wolfgang; Winkler, Frank (Neuro-Oncology, 2021)
Malignant gliomas including glioblastomas are characterized by a striking cellular heterogeneity, which includes a subpopulation of glioma cells that becomes highly resistant by integration into tumor microtube (TM)-connected multicellular networks.A novel functional approach to detect, isolate, and characterize glioma cell subpopulations with respect to in vivo network integration is established, combining a dye staining method with intravital two-photon microscopy, Fluorescence-Activated Cell Sorting (FACS), molecular profiling, and gene reporter studies.Glioblastoma cells that are part of the TM-connected tumor network show activated neurodevelopmental and glioma progression gene expression pathways. Importantly, many of them revealed profiles indicative of increased cellular stemness, including high expression of nestin. TM-connected glioblastoma cells also had a higher potential for reinitiation of brain tumor growth. Long-term tracking of tumor cell nestin expression in vivo revealed a stronger TM network integration and higher radioresistance of the nestin-high subpopulation. Glioblastoma cells that were both nestin-high and network-integrated were particularly able to adapt to radiotherapy with increased TM formation.Multiple stem-like features are strongly enriched in a fraction of network-integrated glioma cells, explaining their particular resilience.
Gesehen am 09.03.2022
Published: 15 December 2020